Clinicopathologic characteristics and predictive nomogram of skip lymph node metastasis in gastric cancer - Zhang, Xinwei; Du, Yuwei; Li, Yuegang; Xue, Chi; Zhu, Zhi (Frontiers in Oncology, 2025)
BackgroundLymph node (LN) status is an independent factor affecting the prognosis of gastric cancer patients. Skip metastasis is a pattern of LN metastasis across a peritumoral (PT) area to an extra-peritumoral (EP) area. The purpose of the present study was to determine the clinical characteristics and establish a predictive nomogram for skip metastasis in gastric cancer.MethodsWe reviewed the records of 1657 gastric cancer patients at the First Affiliated Hospital of China Medical University. The patients were categorized in four groups: only station II (skip group); only station I (PT-only group); station I and station II (PT+EP group); and no metastatic LNs (N0 group). The clinical characteristics between the skip group and the other three groups were compared.ResultsThe incidence of skip metastasis was 3.3% (55/1657) among the gastric cancer patients. The most common locations of skip metastasis were the No. 7 (50.9%), No. 8a (32.7%), No. 9 (21.8%), and No. 1 groups (20.0%). The skip group had significant differences compared to the PT+EP group in pN stage, Borrmann type, pT stage and location, as predictors in the nomogram for prediction of skip metastasis. The area under the ROC curve was 0.908.ConclusionsThis study identified key risk factors for skip lymph node metastasis and developed the first clinically applicable predictive model. The resulting nomogram demonstrated high accuracy in risk stratification, providing a visual tool to optimize lymph node dissection strategies. These findings support incorporating metastatic location into gastric cancer staging systems and the location of LN metastasis should be considered to improve the LN staging.